2018
DOI: 10.4149/gpb_2018007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-term Pilates exercise on selected blood parameters

Abstract: The aim of our prospective, interventional, pre-post, single arm study was to supplement the lack of knowledge of the effect of short-term Pilates intervention on selected blood parameters of healthy women. Female volunteers were recruited for 2-weeks Pilates intervention. Blood has been collected and anthropometric parameters were measured before and after exercise period (EP). Plasma insulin, cortisol, and dehydroepiandrosterone sulphate levels, erythrocyte antioxidant activity, glutathione levels, NK cytoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
0
8
0
1
Order By: Relevance
“…There is a strong association between the type of PA and benefits to the immune system. PA, such as Pilates training performed for 180 min per week, during two weeks of acute PA, improves the innate immune response in adult women, as detected by increased NK cell lytic activity and decreased monocyte chemotactic protein-1 (MCP-1) [ 96 , 97 ]. Bicycle ergometry performed for six minutes at 55% of VO 2 max or for 30 min at 11.11 km/h increases the number of leukocytes (by ~36%), granulocytes (by ~29%), lymphocytes (by ~46%), and monocytes (by ~68%) in circulating blood [ 78 , 80 ].…”
Section: Physical Health Benefits Of Pamentioning
confidence: 99%
“…There is a strong association between the type of PA and benefits to the immune system. PA, such as Pilates training performed for 180 min per week, during two weeks of acute PA, improves the innate immune response in adult women, as detected by increased NK cell lytic activity and decreased monocyte chemotactic protein-1 (MCP-1) [ 96 , 97 ]. Bicycle ergometry performed for six minutes at 55% of VO 2 max or for 30 min at 11.11 km/h increases the number of leukocytes (by ~36%), granulocytes (by ~29%), lymphocytes (by ~46%), and monocytes (by ~68%) in circulating blood [ 78 , 80 ].…”
Section: Physical Health Benefits Of Pamentioning
confidence: 99%
“…It has been demonstrated that PT has a beneficial impact on adipokine levels in overweight women when used for 12 weeks, three days per week for 60 minutes [ 13 ] , as well as serum levels of certain inflammatory markers such as C reactive protein in sedentary women with overweight [ 14 ] . Researchers have also shown that PT is a suggested physical activity to promote health and boost the immune system [ 15 , 16 ] . Gronesova et al [ 16 ] reported that 40 weeks were effective in improving natural killer immune cells response and inflammatory milieu in plasma of healthy women [ 16 ] .…”
Section: Introductionmentioning
confidence: 99%
“…This protection is likely mediated through weight control and hormonal influences such as impairing serum insulin levels ( 3 ) and estrogens. When exercising, metabolism increases ( 4 ), the cardiovascular function accelerates ( 5 ), and blood parameters ( 6 ) seem to be affected. The endocrine system seems to play an important role in those changes ( 7 ).…”
Section: Introductionmentioning
confidence: 99%